The Data Shake Opportunities and Obstacles for Urban Policy Making - Concilio, Grazia; Pucci, Paola; Raes, Lieven; Mareels, Geert (PoliMI SpringerBriefs,, 2021)
This open access book represents one of the key milestones of PoliVisu, an H2020 research and innovation project funded by the European Commission under the call "Policy-development in the age of big data: data-driven policy-making, policy-modelling and policy-implementation". It investigates the operative and organizational implications related to the use of the growing amount of available data on policy making processes, highlighting the experimental dimension of policy making that, thanks to data, proves to be more and more exploitable towards more effective and sustainable decisions. The first section of the book introduces the key questions highlighted by the PoliVisu project, which still represent operational and strategic challenges in the exploitation of data potentials in urban policy making. The second section explores how data and data visualisations can assume different roles in the different stages of a policy cycle and profoundly transform policymaking.